2011
DOI: 10.1096/fj.11-192468
|View full text |Cite
|
Sign up to set email alerts
|

A novel treatment strategy for ovarian cancer based on immunization against zona pellucida protein (ZP) 3

Abstract: We tested the principle of treating malignant ovarian tumors by vaccination against their ectopically expressed protein, zona pellucida glycoprotein (ZP) 3, using as the experimental model the granulosa cell tumors that develop in transgenic mice expressing the simian virus 40 T-antigen under the inhibin-α promoter (inhα/Tag). We found high ZP3 expression in granulosa cell tumors of the transgenic mice, in human surface ovarian cancer and granulosa cell lines, and in human granulosa cell tumors and their metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…A recent study ( 10 ) based on correlating expression arrays and array comparative genomic hybridization (CGH) data also found that UBAP2L showed amplification expression in HCC, which is one of the early genomic events associated with HCC development. Naz and Dhandapani ( 11 ) reported that UBAP2L showed 97% homology at the nucleotide and amino acid sequences with ZPC-interacting protein involved in malignant ovarian tumors ( 15 ). Furthermore, Sudhir et al ( 16 ) identified UBAP2L as a novel target of mitogen-activated protein kinase (MAPK) family kinases that acts as a downstream component of Ras-mediated signaling and has an important role in the pathogenesis of certain types of human cancer, such as lung cancer and glioma ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study ( 10 ) based on correlating expression arrays and array comparative genomic hybridization (CGH) data also found that UBAP2L showed amplification expression in HCC, which is one of the early genomic events associated with HCC development. Naz and Dhandapani ( 11 ) reported that UBAP2L showed 97% homology at the nucleotide and amino acid sequences with ZPC-interacting protein involved in malignant ovarian tumors ( 15 ). Furthermore, Sudhir et al ( 16 ) identified UBAP2L as a novel target of mitogen-activated protein kinase (MAPK) family kinases that acts as a downstream component of Ras-mediated signaling and has an important role in the pathogenesis of certain types of human cancer, such as lung cancer and glioma ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ZP3 expression has been found in 100% of normal tissue, it has also been present in 64% of OSCC samples which leads to an exclusion of ZP3 for a good potential cancer-specific biomarker. However, in mice, ZP3 has been used as treatment approach against ovarian cancer based upon immunization against murine ZP3 [ 15 ]. A recent publication deals with ZP3 as new prognostic and potential therapeutic marker in renal clear cell carcinoma showing ZP3 30-fold higher expressed in tumor versus normal counterparts [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein has already been detected in normal and cancerous tissues, particularly investigated in prostate cancer cells [ 14 ]. A treatment strategy in mice for ovarian cancer that is based upon immunization against murine ZP3 has also been published [ 15 ]. All in all, aware of these observations, we consider ZP3 to be a potent candidate for OSCC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the expression in female and male gametes under physiological circumstances, ectopic expression of ZP3 has been shown in cancer ( 20 22 ). ZP3 protein was abundantly expressed in granulosa cell tumors, a rare form of ovarian cancer, and was unexpectedly shown to localize to the cytoplasm ( 20 ), contradicting the plasma membrane localization and extracellular secretion of ZP3 in oocytes. Also in the prostate cancer cell line PC3, ZP3 protein appeared dominantly cytoplasmic ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the enriched expression of ZP3 in cancer versus normal tissue provides a therapeutic opportunity, whether ZP3 is secreted from cancer cells or not is an important strategic determinant for the development of a cancer immunotherapy based on active or passive immunization. The proof-of-principle for the development of a ZP3-based cancer vaccine for active immunization has been demonstrated in a transgenic mouse model of ovarian granulosa cell cancer ( 20 ).…”
Section: Introductionmentioning
confidence: 99%